2006
DOI: 10.1021/jf052570u
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Amino Acid Composition of Soybeans (Glycine max) by Near-Infrared Spectroscopy

Abstract: Calibration equations for the estimation of amino acid composition in whole soybeans were developed using partial least squares (PLS), artificial neural networks (ANN), and support vector machines (SVM) regression methods for five models of near-infrared (NIR) spectrometers. The effects of amino acid/protein correlation, calibration method, and type of spectrometer on predictive ability of the equations were analyzed. Validation of prediction models resulted in r 2 values from 0.04 (tryptophan) to 0.91 (leucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 9 publications
3
79
2
1
Order By: Relevance
“…However, although our model takes into account some variability between laboratories for the analysis of NDF, this analysis of NDF should be validated considering its inter-laboratory variability (Mertens, 2003). For dEAA contents, although the content NDF provides a valid estimate of dEAA, if the total essential amino acid (tEAA) content is available easily, for example by analysis by NIRS (near-infrared spectroscopy) (Kovalenko et al, 2006), the dEAA prediction model using the tEAA is more accurate with lower RMSE and a higher R 2 .…”
Section: Prediction Of Standardized Ileal Digestibility Of Essential mentioning
confidence: 99%
“…However, although our model takes into account some variability between laboratories for the analysis of NDF, this analysis of NDF should be validated considering its inter-laboratory variability (Mertens, 2003). For dEAA contents, although the content NDF provides a valid estimate of dEAA, if the total essential amino acid (tEAA) content is available easily, for example by analysis by NIRS (near-infrared spectroscopy) (Kovalenko et al, 2006), the dEAA prediction model using the tEAA is more accurate with lower RMSE and a higher R 2 .…”
Section: Prediction Of Standardized Ileal Digestibility Of Essential mentioning
confidence: 99%
“…Eschun and He (2004) also reported that 98.4 per cent water in raw pulp of A. vera while discussing the use of A. vera in connection with pharmaceutical and cosmetic industries. Though the protein content of soybean whey in the present study is low (1.61%), soya whey is considered as a good source of nutrients because of the presence of several essential amino acids which are in balanced amount resulting in high protein efficiency ratio (Kovalenko et al, 2006). The roots of C. borivilianum and the stem of T. cordifolia exhibited better values for protein (8.41 and 12.91, respectively) which are in conformity as reported by Singh et al (2003).…”
Section: Results and Discussion Proximate Composition And Mineral Conmentioning
confidence: 72%
“…Eschun and He (2004) also reported 98.4 per cent water in raw pulp of A. vera while discussing the use of A. vera in connection with pharmaceutical and cosmetic industries. Although the protein content of the soybean whey in the present study is low (1.61%), soya whey is considered as a good source of nutrient because of the presence of several essential amino acids which are in balanced amount resulting in high protein efficiency ratio (Kovalenko et al, 2006). The roots of C. borivilianum and the stem of T. cordifolia exhibited better values for protein (8.41 and 12.91, respectively) which are in conformity as reported by Singh et al, (2003).…”
Section: Proximate Composition and Mineral Content Of The Selected Plmentioning
confidence: 72%